A ideologia do capital nas políticas públicas de incentivo à leitura: uma análise da política de incentivo à leitura do município de Francisco Beltrão - PR (2005-2015) - Avila, Keissiane Michelotti Geittenes de (2016)
In recent decades the incentive to reading was beyond school gaining support in hegemonic sectors of civil society like companies and banks until becoming State policy. The slogans of the reading incentive policies, with reductionist attributes, forged a common sense reading about the need to eradicate inequalities, produce peace, include, form the citizen and considerably transform education. The research analyzes the reading incentive policy at the federal, state establishing an incentive mark and the motivation to reading in the years 2007-2014 and city of Francisco Beltrão-PR in the period of 2005-2015. Part of the following issues: What is the reason of the State and different sectors of society encourage reading? Is there an against ideological proposal? The objective of the reasearch was to identify and analyse the contradictions of public policies to reading encourage, unravel the alienating and ideological approaches present in the programs, campaigns and projects and the rebounds of such ideological context in the city policy of Francisco Beltrão-PR. Specifically, understand the role of the Education Department for maintaining the current order, consolidating pedagogy of hegemony and its relationship with the encouragement to reading. . It was developed through analysis of documents that guide national, international, business and state and city plans for reading policies. To collect empirical data within the city politicy of Francisco Beltrão - PR, it was used semi structured complemented by analysis of documents that subsidized them. The data were analyzed from Chauí (1994), Marx (1998), Marx e Engels (1998, 2007), Mészáros (2007, 2008, 2012), Saviani (1996, 2004, 2013) and other authors that criticize the neoliberalism and its Pedagogy of hegemony. We situate reading from a critical approach guided by Britto (1999, 2003, 2009), Freire (2000, 2015) e Silva (1986, 1988, 1998a, 1998b, 1999a, 1999b, 1999c, 2009) understanding it in the context of knowledge democratization and combating alienation whose views turn to awareness, active participation and require from the educator a political position before society. The results show that reading policies are presented as a salvationist strategy for the popular classes and mask the interests of capital made consensus through its Pedagogy of hegemony. Distance themselves from a motivation to reading while moving critical consensus.They point out that reading policies fall within the context of capitalist social relations consolidated the new relations of production as a result of the neoliberal model in which the State reduces its role and delegate to individuals the responsibility for the structural problems of society. The State, in this sense, becomes educator to redefine the task of forming the new man adapted to bourgeois sociability. Reading incentive policies are part of this educator State project. Cumpling with UNESCO parameters: education throughout life and competence with knowledge. The city policy is similar to national policies in the question citizenship, social inclusion and responsibility.